Peran dan Transformasi Pemandu Wisata di Era Digital: Sebuah Systematic Literature Review - Pusparani, Pusparani; Herienda, Florensia; Adriani, Hanni; Hutagalung, M. Husen; Pradhipta, RMW Agie (Jurnal Ilmiah Pariwisata, 2025)
TThis study aims to map the roles and transformations of tour guides in the digital era through a systematic review of current empirical evidence. The research employed a Systematic Literature Review (SLR) guided by the PRISMA framework, drawing data from Scopus, Web of Science, and Google Scholar (1995–2025). A total of 33 articles met the inclusion criteria and were thematically analyzed and narratively synthesized. The findings reveal three complementary thematic clusters. The first cluster highlights professional competencies, interpretative, interpersonal, and managerial dimensions as core service attributes that enhance service quality, satisfaction, and behavioral intentions. The second cluster emphasizes affective dimensions, such as emotional labor, empathy, and rapport, as psychological mechanisms that transform service quality into memorable tourism experiences, leading to loyalty and positive word-of-mouth. The third cluster identifies the digital transformation of tour guiding through mobile applications, AR/VR/XR, virtual or livestream tours, and AI-assisted collaboration, which strengthen interactivity, immersion, personalization, and eWOM. In conclusion, the synergy of competence, affect, and digital capability creates an experiential value chain linking service quality to satisfaction, loyalty, and destination image. Future research is recommended to examine tour guide well-being, evaluate human–AI co-guiding, employ multi-group SEM, conduct bibliometric/meta-analyses, and compare outcome-based versus input-based certification systems. Keywords: tour guide transformation, digital tourism, systematic literature review